Layered-structure positive electrode material and pole piece of sodium-ion battery and preparation method of layered-structure positive electrode material and pole piece
By using Na0.85Li0.15Mg0.05Ni0.1Mn0.7-xAlxO2 positive electrode material doped with various transition group elements, the problem that the P2-O2 phase transition material is prone to occur at high voltages is solved, and better cycle stability and energy density are achieved.
Patent Information
- Application Number
- CN202411932192.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion battery positive electrode materials are prone to P2-O2 phase transitions at high voltages, resulting in structural damage and poor material stability, which in turn causes capacity attenuation.
Na0.85Li0.15Mg0.05Ni0.1Mn0.7-xAlxO2 (0≤x≤0.06) is used as the positive electrode material. The cyclic stability and structural stability of the material are improved by doping a variety of transition group elements through the ion battery layered oxide positive electrode material, combined with solid phase method and wet ball milling and other preparation methods.
It achieves a smaller volume change rate and better stability during charging and discharging. Compared with traditional P2 layered oxides, it has better stability in water or air, extends the cycle life of the battery and increases the energy density.
Smart Images

Figure CN119674035A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery layered structure positive electrode material, a pole piece and a preparation method. Background Art
[0002] Sodium-ion batteries have received extensive attention for large-scale energy storage due to the abundance of sodium resources and low cost worldwide. However, in order to improve the energy density and operating voltage of these batteries, the development of high-performance cathode materials is crucial. Research on cathode materials in recent years has shown that transition metal layered oxides (NaxTMO2, TM transition metals, Ti, Mn, Fe, Co, Ni, Cu, etc.) have great potential for practical applications due to their simple synthesis, excellent electrochemical properties, and ease of industrialization.
[0003] For P2- and O3-type sodium-based layered oxides, where O and P correspond to the coordination environment of sodium ions in the alkali metal layer (O represents octahedron and P represents triangular prism), the number represents the minimum number of layers in the periodic sequence formed by stacking oxygen atoms (2 corresponds to ABBAABBA…, 3 corresponds to ABCABC…). O3-phase cathodes generally exhibit higher specific capacity than P2-phase cathodes due to the higher initial Na content but poor rate and cycling performance due to the poor diffusion ability of Na+ at the octahedral sites. Compared with the O3 phase, the P2 framework has higher ionic conductivity and lower diffusion barrier, which provides an opportunity for its excellent rate / cycling performance and stable structural properties, making it a very promising cathode material for sodium-ion batteries. Typical P2-type Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 has 160mAhg when the working voltage is greater than 3.7V -1 However, when charged to 4.2 V, the Na + As the number decreases, the electrostatic repulsion between two adjacent TMO2 plates increases, which will drive the transition metal layer to slide relative to each other to reduce the repulsive force of the system, thereby achieving a stable structure and causing the so-called P2-O2 phase transition, which introduces drastic volume changes, leading to structural damage and poor material stability, resulting in more serious capacity attenuation. Summary of the invention
[0004] In view of the shortcomings of the prior art, one of the purposes of the present application is to provide a sodium ion battery layered structure positive electrode material, a pole piece and a preparation method, which have the advantage of good stability.
[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:
[0006] A sodium ion battery layered structure positive electrode material, the chemical formula of the positive electrode material is Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.7-x Al x O2(0≤x≤0.06).
[0007] The present application also discloses a method for preparing a sodium ion battery layered structure positive electrode material, comprising the following steps: step (1), weighing a sodium source compound, a manganese source compound, a nickel source compound, an aluminum source compound, a magnesium source compound and a lithium source compound according to the molar ratio of each element, wherein the sodium source is in excess of 2% to 5% based on the sodium element; after weighing, first fully mixing in a hand grinder, then adding a dispersant for wet ball milling, and then drying at high temperature to obtain a precursor; step (2), preheating and keeping the precursor in a tubular furnace under an atmosphere, cooling to room temperature in the furnace, and then grinding in an agate mortar, and then placing the sample in a tubular furnace for calcination and keeping warm in an atmosphere, and cooling to a certain temperature in the furnace to obtain a layered oxide positive electrode material.
[0008] In a preferred example, the present application can be further configured as follows: in step (1), the dispersant is methanol, acetone or anhydrous ethanol.
[0009] In a preferred example, the present application can be further configured as follows: in step (2), the calcination temperature is 800-1200°C, the heating rate is 2-8°C / min, the preheating time is 6-24h, the calcination time is 6-24h, the preheating and calcination atmospheres include but are not limited to air atmosphere, argon atmosphere, oxygen atmosphere, helium atmosphere, nitrogen atmosphere, and the sampling temperature during furnace cooling is 100-800°C.
[0010] The present application also discloses a method for preparing a sodium ion battery layered structure positive electrode sheet, comprising the following steps: step (1) grinding the positive electrode material, the conductive additive and the binder in a mass ratio of 8:1:1, 7:2:1 or 85:10:5 to be uniform; step (2) adding NMP solution to the powder in step (1) in a ratio of 1 / 1 to 1.5 (g / ml) to the active material, stirring on a magnetic stirrer for 0.5 to 8 hours to obtain a slurry; step (3) using a coater to evenly coat the slurry on an aluminum foil with a thickness of 50 to 250 μm; and step (4) drying in a vacuum drying oven at 80 to 120° C. for 5 to 12 hours.
[0011] This application has the following advantages:
[0012] (1) The present application is a layered oxide positive electrode material for ion batteries doped with multiple transition elements. Compared with single-element doped layered oxide positive electrode materials, it has better cycle stability and a smaller volume change rate during charge and discharge. Compared with traditional P2-type layered oxides, the multi-element doped structure has better stability in water or air.
[0013] (2) The sodium source used in this application is more extensive and cheaper than lithium, so the raw materials of sodium-ion batteries are easier to obtain, and the manufacturing cost of sodium-ion batteries is relatively low, which may make the production cost of batteries more economical. Sodium-ion batteries have a higher battery capacity and can store more charge in the same volume, which means that sodium-ion batteries have the potential to provide higher energy density.
[0014] (3) The mining and recovery of the sodium source used in this application has little impact on the environment. Compared with lithium-ion batteries, sodium-ion batteries have more environmental advantages. In addition, the preparation method of the present invention is efficient and simple, suitable for large-scale industrial production, and easy to promote and apply in industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a scanning electron microscope (SEM) morphology image of a battery layered oxide positive electrode material particle prepared in Example 1;
[0016] Figure 2 This is a scanning electron microscope (SEM) morphology image of a battery layered oxide positive electrode material particle prepared in Example 2;
[0017] Figure 3 This is a scanning electron microscope (SEM) morphology image of a sodium ion battery layered oxide positive electrode material particle prepared in Example 3;
[0018] Figure 4 This is an XRD spectrum of a layered oxide positive electrode material prepared in Example 1;
[0019] Figure 5 This is a comparison chart of the rate performance of the sodium ion battery positive electrode materials obtained in Example 1 and Comparative Example 1.
[0020] Figure 6 This is a comparison chart of the cycle performance of the sodium ion battery positive electrode materials obtained in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0021] The present application is further described in detail below in conjunction with the accompanying drawings.
[0022] Reference Figure 1-Figure 6 , is a sodium ion battery layered structure positive electrode material disclosed in this application, the chemical formula of the positive electrode material is Na 0.85 Li0.15 Mg 0.05 Ni 0.1 Mn 0.7-x Al x O2(0≤x≤0.06).
[0023] Comparative Example 1:
[0024] This comparative example provides a method for preparing a positive electrode material and a pole piece for a sodium ion battery, the chemical formula of which is Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.7 O2, comprising: Step 1: Preparation of positive electrode material by solid phase method
[0025] (1) fully mixing a sodium source, a manganese source, a nickel source, a lithium source, and a magnesium source;
[0026] (2) placing the mixture in a drying oven for drying and then transferring it into an alumina crucible;
[0027] (3) The alumina crucible is placed in a tube furnace and sintered in an oxygen atmosphere to obtain a positive electrode material for a battery.
[0028] In some preferred embodiments, the raw materials in (1) are weighed according to the stoichiometric ratio of 0.85:0.15:0.05:0.1:0.7, and the mixture is hand-milled for 30 minutes, placed in a ball mill, anhydrous ethanol is added as a dispersant, and ball-milled at 300 r / min for 8 hours.
[0029] In some preferred embodiments, in (2), the drying temperature is 100° C. and the drying time is 5 h.
[0030] In some preferred embodiments, in said (3), the heating rate is 5°C / min, the temperature is kept at 950°C for 15h, and then the temperature is cooled to 100°C to obtain the positive electrode material of the battery.
[0031] Step 2: Preparation of Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.7 O2 positive electrode
[0032] (1) The positive electrode material prepared above was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, hand-grinded until the mixture was uniform, and N-methylpyrrolidone was added, with the mixed powder and its mass volume ratio being 1:1.5. After being placed on a magnetic stirrer and stirred at room temperature for 12 hours, the slurry was coated on an aluminum foil with a thickness of 100 μm, and then placed in a vacuum drying oven at 80°C for 12 hours to obtain a pole piece;
[0033] (2) 2032 button cells were assembled using metallic sodium as the negative electrode. The entire assembly process was carried out in a glove box filled with argon. The assembly order was: negative electrode shell, metallic sodium, glass fiber separator (GF / D), electrolyte (1M NaClO4 in EC:DC=1:1 vol%), positive electrode sheet (14 mm), gasket, elastic ring, positive electrode shell; the charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System.
[0034] Example 1
[0035] This embodiment provides a method for preparing a positive electrode material and a pole piece for a sodium ion battery, wherein the chemical formula is Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.68 Al 0.02 O2, including:
[0036] Step 1: Preparation of cathode materials by solid phase method
[0037] (1) fully mixing a sodium source, a manganese source, a nickel source, a lithium source, a magnesium source, and an aluminum source;
[0038] (2) placing the mixture in a drying oven for drying and then transferring it into an alumina crucible;
[0039] (3) The alumina crucible is placed in a tube furnace and sintered in an oxygen atmosphere to obtain a positive electrode material for a battery.
[0040] In some preferred embodiments, the raw materials in (1) are weighed according to the stoichiometric ratio of 0.85:0.15:0.05:0.1:0.68:0.02, 2.37 g of sodium carbonate (5% excess to make up for the loss of high-temperature sodium), 0.375 g of nickel oxide, 0.1 g of magnesium oxide, 0.325 g of lithium hydroxide, 2.97 g of manganese trioxide, and 0.051 g of aluminum oxide, and hand-milled for 30 min, placed in a ball mill, anhydrous ethanol is added as a dispersant, and ball-milled at 300 r / min for 8 h.
[0041] In some preferred embodiments, in (2), the drying temperature is 100° C. and the drying time is 5 h.
[0042] In some preferred embodiments, in said (3), the heating rate is 5°C / min, the temperature is kept at 950°C for 15h, and then the temperature is cooled to 100°C to obtain the positive electrode material of the battery.
[0043] Step 2: Preparation of Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.68 Al 0.02 The preparation process of the O2 positive electrode sheet is the same as that of comparative example 1. The charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System, with a current density of 1C (1C = 100 mA / g), a voltage range of 1.5-4.5V, and a capacity retention rate of 75% after 200 cycles.
[0044] Figure 1 The scanning electron microscope morphology image of the product particles obtained in Example 1 shows that the sample is a lamellar particle with a smooth surface and a particle diameter of about 2-4 μm. In the image, many stacked lamellar structures can be seen, forming an arrangement similar to stacked slabs. There are tiny gaps and gaps between these layered structures, which may help the sodium ions to escape and embed during the charge and discharge process. Observed at high magnification, it can be seen that the surface of the layered structure is smooth and uniform, showing good crystallinity and grain morphology.
[0045] Figure 4 This is the XRD diagram of the product obtained in this example. It can be seen that the product has good crystal morphology and complete crystal form, and the phase composition is a single P2 phase without the presence of other impurities, indicating that the system is a sodium ion battery positive electrode material with a P2 layered structure.
[0046] Figure 5 The rate diagrams of Example 1 and Comparative Example 1 at current densities of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C and 0.1C in the voltage range of 1.5 to 4.5V are shown. It can be seen from the figure that the capacity of Example 1 is higher than that of Comparative Example 1 at all current densities. Even at a high current of 10C, the discharge specific capacity is 40mAh / g. Compared with Comparative Example 1, Example 1 can still maintain a higher capacity retention rate, and when it returns to 0.1C, the discharge specific capacity returns to 135mAh / g. Therefore, the aluminum element stabilizes the structure of the material and improves the rate and performance of the battery.
[0047] Figure 6 The cyclic stability curves of Example 1 and Comparative Example 1 after 200 cycles at 1C (1C=100 mA / g) current density and 1.5-4.5 V voltage range. After 200 cycles, the capacity retention rate of Comparative Example 1 is 73%, and the capacity retention rate of Example 1 after 200 cycles is 75%.
[0048] Example 2
[0049] This embodiment provides a method for preparing a positive electrode material and a pole piece for a sodium ion battery, wherein the chemical formula is Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.66 Al 0.04 O2, including:
[0050] Step 1: Preparation of cathode materials by solid phase method
[0051] (1) fully mixing a sodium source, a manganese source, a nickel source, a lithium source, a magnesium source, and an aluminum source;
[0052] (2) placing the mixture in a drying oven for drying and then transferring it into an alumina crucible;
[0053] (3) The alumina crucible is placed in a tube furnace and sintered in an oxygen atmosphere to obtain a positive electrode material for a battery.
[0054] In some preferred embodiments, the raw materials in (1) are weighed according to the stoichiometric ratio of 0.85:0.15:0.05:0.1:0.66:0.04, 2.37 g of sodium carbonate (5% excess to make up for the loss of high-temperature sodium), 0.375 g of nickel oxide, 0.1 g of magnesium oxide, 0.325 g of lithium hydroxide, 2.87 g of manganese trioxide, and 0.102 g of aluminum oxide, and hand-milled for 30 min, placed in a ball mill, anhydrous ethanol is added as a dispersant, and ball-milled at 300 r / min for 8 h.
[0055] In some preferred embodiments, in (2), the drying temperature is 100° C. and the drying time is 5 h.
[0056] In some preferred embodiments, in said (3), the heating rate is 5°C / min, the temperature is kept at 950°C for 15h, and then the temperature is cooled to 100°C to obtain the positive electrode material of the battery.
[0057] Step 2: Preparation of Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.66 Al 0.04 The preparation process of the O2 positive electrode sheet is the same as that of comparative example 1. The charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System, with a current density of 1C (1C = 100 mA / g), a voltage range of 1.5-4.5V, and a capacity retention rate of 70% after 200 cycles.
[0058] Figure 2This is a scanning electron microscope image of the product particles obtained in Example 2. It can be seen that the sample is a lamellar particle with a smooth surface and a particle diameter of about 2-4 μm. In the image, many stacked lamellar structures can be seen, forming an arrangement similar to stacked stone slabs.
[0059] Example 3
[0060] This embodiment provides a method for preparing a sodium ion battery positive electrode material and a pole piece thereof, wherein the chemical formula is Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.64 Al 0.06 O2, including:
[0061] Step 1: Preparation of cathode materials by solid phase method
[0062] (1) fully mixing a sodium source, a manganese source, a nickel source, a lithium source, a magnesium source, and an aluminum source;
[0063] (2) placing the mixture in a drying oven for drying and then transferring it into an alumina crucible;
[0064] (3) The alumina crucible is placed in a tube furnace and sintered in an oxygen atmosphere to obtain a positive electrode material for a battery.
[0065] In some preferred embodiments, the raw materials in (1) are weighed according to the stoichiometric ratio of 0.85:0.15:0.05:0.1:0.66:0.04, 2.37 g of sodium carbonate (5% excess to make up for the loss of high-temperature sodium), 0.375 g of nickel oxide, 0.1 g of magnesium oxide, 0.325 g of lithium hydroxide, 2.78 g of manganese trioxide, and 0.15 g of aluminum oxide, and hand-grinded for 30 min, placed in a ball mill, anhydrous ethanol was added as a dispersant, and ball-milled at 300 r / min for 8 h.
[0066] In some preferred embodiments, in (2), the drying temperature is 100° C. and the drying time is 5 h.
[0067] In some preferred embodiments, in said (3), the heating rate is 5°C / min, the temperature is kept at 950°C for 15h, and then the temperature is cooled to 100°C to obtain the positive electrode material of the battery.
[0068] Step 2: Preparation of Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.64 Al 0.06The preparation process of the O2 positive electrode sheet is the same as that of comparative example 1. The charge and discharge cycle test was carried out in the Wuhan Blue Electric Battery Test System, with a current density of 1C (1C = 100 mA / g), a voltage range of 1.5-4.5V, and a capacity retention rate of 67% after 200 cycles.
[0069] Figure 3 This is a scanning electron microscope image of the product particles obtained in Example 3. It can be seen that the sample is a lamellar particle with a smooth surface and a particle diameter of about 2-4 μm. In the image, many stacked lamellar structures can be seen, forming an arrangement similar to stacked stone slabs.
[0070] The implementation principle of this embodiment is: the ion battery layered oxide positive electrode material doped with multiple transition elements has better cycle stability than the layered oxide positive electrode material doped with a single element, and has a smaller volume change rate during the charge and discharge process. Moreover, compared with the traditional P2-type layered oxide, the multi-element doped structure has better stability in water or air.
[0071] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A sodium ion battery layered structure positive electrode material, characterized in that: The chemical formula of the positive electrode material is Na 0.85 Li 0.15 Mg 0.05 Ni 0.1 Mn 0.7-x Al x O2(0≤x≤0.06).
2. The method for preparing a sodium ion battery layered structure positive electrode material according to claim 1, characterized in that: The method comprises the following steps: step (1), weighing a sodium source compound, a manganese source compound, a nickel source compound, an aluminum source compound, a magnesium source compound and a lithium source compound according to the molar ratio of each element, wherein the sodium source is in excess of 2% to 5% based on the sodium element, and after weighing, first fully mixing in a hand mill, then adding a dispersant for wet ball milling, and then drying at high temperature to obtain a precursor; step (2), preheating and heat-insulating the precursor in a tubular furnace under an atmosphere, cooling to room temperature with the furnace, and then grinding in an agate mortar, and then placing the sample in a tubular furnace for calcination and heat-insulation under an atmosphere, and cooling to a certain temperature with the furnace to obtain a layered oxide positive electrode material.
3. The method for preparing a sodium ion battery layered structure positive electrode material according to claim 2, characterized in that: In step (1), the dispersant is methanol, acetone or anhydrous ethanol.
4. The method for preparing a sodium ion battery layered structure positive electrode material according to claim 2, characterized in that: In step (2), the calcination temperature is 800-1200° C., the heating rate is 2-8° C. / min, the preheating time is 6-24 h, the calcination time is 6-24 h, and the sampling temperature during furnace cooling is 100-800° C.
5. A method for preparing a layered positive electrode sheet for a sodium ion battery, characterized in that: The method comprises the following steps: step (1) grinding the positive electrode material, the conductive additive and the binder uniformly in a mass ratio of 8:1:1, 7:2:1 or 85:10:5; step (2) adding NMP solution to the powder in step (1) in a ratio of 1 / 1 to 1.5 (g / ml) to the active material, stirring on a magnetic stirrer for 0.5 to 8 hours to obtain a slurry; step (3) coating the slurry uniformly on an aluminum foil with a coater to a thickness of 50 to 250 μm; and step (4) drying in a vacuum drying oven at 80 to 120° C. for 5 to 12 hours.
Citation Information
Patent Citations
Doped P2 type layered sodium nickel manganese oxide positive electrode material and preparation method thereof
CN115650318A
Manganese-based layered oxide positive electrode material and preparation method and application thereof
CN116314739A
Preparation method of long-circulation sodium ion battery positive electrode material and sodium ion battery
CN116895744A
Sodium-ion battery P2 type nickel-manganese-based layered oxide positive electrode material and preparation method thereof
CN118919714A
Vacancy-type sodium ion positive electrode material, preparation method therefor, and use thereof
WO2024040925A1